2020
DOI: 10.1177/0003134820923297
|View full text |Cite
|
Sign up to set email alerts
|

Transdiaphragmatic Chest Wall Herniation

Abstract: Background The combination of traumatic simultaneous diaphragmatic rupture and chest wall herniation remains rare, with 42 cases of traumatic transdiaphragmatic intercostal hernia (TDIH) reported in the literature since 1946. An accurate count of cases is difficult to obtain, as TDIH nomenclature has been variable. 1 - 5 Risk factors for traumatic TDIH are not well established. As these injuries are uncommon, best management techniques have yet to be established. Reported repair techniques include primary clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…There remains debate regarding the optimal management of the IH component, especially considering the demonstrated chronic presentation in the obese patient. Other authors have reported failure rates of up to 66% for surgical repair using sutures with or without single layer mesh, in keeping with our experience 20,21 . We encountered some failures with suture repair and extrathoracic mesh repair, before moving to the double layer mesh repair (DLMR).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There remains debate regarding the optimal management of the IH component, especially considering the demonstrated chronic presentation in the obese patient. Other authors have reported failure rates of up to 66% for surgical repair using sutures with or without single layer mesh, in keeping with our experience 20,21 . We encountered some failures with suture repair and extrathoracic mesh repair, before moving to the double layer mesh repair (DLMR).…”
Section: Discussionsupporting
confidence: 86%
“…Other authors have reported failure rates of up to 66% for surgical repair using sutures with or without single layer mesh, in keeping with our experience. 20,21 We encountered some failures with suture repair and extrathoracic mesh repair, before moving to the double layer mesh repair (DLMR). While we have not sought patient-reported quality of life outcome data in this study, the surgical results of DLMR appear satisfactory.…”
Section: Discussionmentioning
confidence: 99%